Diquat and Paraquat Analysis in Rice using a Zwitterionic Hydrophilic Interaction Chromatography – tandem Mass Spectrometry - Thanh-Nho Nguyen; Cong-Hau Nguyen; Nhu-Quynh Nguyen (Indonesian Journal of Chemical Analysis (IJCA), 2022)
The analysis of polar herbicides by liquid chromatography-tandem mass spectrometry (LC-MS/MS) is challenging due to their complicated interactions. Diquat and paraquat, the bipyridilium group of polar herbicides, are widely used worldwide. This study aimed to optimize analytical conditions of diquat and paraquat in rice matrix using a hydrophilic interaction liquid chromatography column (Obelisc R; 2.1 x 150 mm, 5 µm). The mixtures of acetonitrile and ammonium formate buffer in water were used as mobile phase. All buffer solutions were acidified to a pH of 2.5 using concentrated formic acid. The results showed that 10 mM buffer concentration of ammonium formate was optimal compared to others, including 5, 20, and 50 mM. A mixture of methanol and water (6:4, v/v) containing 1% formic acid was used as an extractable solvent for sample preparation. Method quantitation limit (MQL) of diquat and paraquat in rice samples was 10 µg kg-1. Recoveries at different concentrations (i.e., 20, 50, and 100 µg kg-1) were higher than 70% for diquat, and 80% for paraquat with RSD < 20%, respectively. Diquat and paraquat in rice samples purchased from the local market were lower than MQL, with good recoveries for standard spiked samples.